Copper(II) ion selective PVC membrane electrode based on S,S'-bis(2-aminophenyl)ethanebis(thioate - Buzuk, Marijo (Array, 2009)
Summary:S,S'-bis(2-aminophenyl)ethanebis(thioate) (APhET) was synthesized and used as ion carrier in the preparation of copper(II) ion selective PVC membrane electrodes. The best performances were obtained by a membrane electrode with the composition: PVC as matrix (66 mg), APhET as ionophore (4 mg), o-NPOE as plasticizer (132 mg) and NaTBP as anionic additive (1/2 mole ratio in respect to APhET). This electrode exhibited a linear potential response to copper(II) in the concentration range 6.0 × 10−6 − 5.0 × 10−2 mol dm−3, with Nernstian slope of 29.5 mV/decade and detection limit down to 4 × 10−6 mol dm−3. It is suitable for copper(II) determination within pH between 4 and 7, and performs well over a period of 3 months. The electrode is selective for copper over a large number of metal ions, except Hg2+. No interference was noticed by chlorides and other examined anions. Described membrane electrode can be used in analytical measurements by direct potentiometry as well in potentiometric titration